Angiopellosis as an Alternative Mechanism of Cell Extravasation. (21st July 2016) - Allen, Tyler A.; Gracieux, David; Talib, Maliha; Tokarz, Debra A.; Hensley, M. Taylor; Cores, Jhon; Vandergriff, Adam; Tang, Junnan; de Andrade, James B.M.; Dinh, Phuong‐Uyen; Yoder, Jeffrey A.; Cheng, Ke
Abstract: Stem cells possess the ability to home in and travel to damaged tissue when injected intravenously. For the cells to exert their therapeutic effect, they must cross the blood vessel wall and enter the surrounding tissues. The mechanism of extravasation injected stem cells employ for exit has yet to be characterized. Using intravital microscopy and a transgenic zebrafish line Tg(fli1a:egpf) with GFP‐expressing vasculature, we documented the detailed extravasation processes in vivo for injected stem cells in comparison to white blood cells (WBCs). While WBCs left the blood vessels by the standard diapedesis process, injected cardiac and mesenchymal stem cells underwent a distinct method of extravasation that was markedly different from diapedesis. Here, the vascular wall undergoes an extensive remodeling to allow the cell to exit the lumen, while the injected cell remains distinctively passive in activity. We termed this process Angio‐pello‐sis, which represents an alternative mechanism of cell extravasation to the prevailing theory of diapedesis. Stem Cells 2017;35:170–180 Video Highlight:https://youtu.be/i5EI-ZvhBps Abstract : A stem cell during the middle of the Angiopellosis process. The cell is in the process of extravasating from the inside the lumen of a blood vessel, into the surrounding area. The endothelial cells of the blood vessel are seen remodeling themselves around the cell, as it is removed from the lumen.